Pengaruh Podcast Sebagai Media Untuk Meningkatkan Self Development Mahasiswa Indonesia (Studi Pada Mahasiswa Indonesia Pendengar Podcast ‘Self Dev By Andreas Bordes’): (Studi Pada Mahasiswa Indonesia Pendengar Podcast ‘Self Dev By Andreas Bordes’) - Fildzah Jonerd Ramadhani; Reni Nuraeni (Jurnal Studi Komunikasi dan Media, 2023)
Self-development is an important aspect that must be owned by students before entering the career world, because to do self-development, it is not enough if you only get knowledge through formal education. Currently, there are many contents that discuss self-development, one of which is the 'Self Dev by Andreas Bordes' podcast. This makes researchers interested in knowing the influence of podcasts on the level of self-development in Indonesian students. This study uses a quantitative method with an intact group comparison type of research. By distributing questionnaires to both groups of Indonesian students, the results are classified as a control group and an experimental group. The classification results aim to see the difference between the two groups. The researcher conducted hypothesis testing in the form of a Mann-Whitney test for both groups of respondents, with the result that there was a significant difference between the two groups. In addition, the experimental group had a higher total score compared to the control group, so it can be concluded that the 'Self Dev by Andreas Bordes' podcast has an influence on improving the self-development of Indonesian students.